Nickel Influences Urease Activity and Calcium Distribution in Tomato Fruits - Macedo, Fernando Giovannetti [UNESP]; Montanha, Gabriel Sgarbiero; Pereira De Carvalho, Hudson Wallace; De Melo, Wanderley Jose [UNESP] (American Chemical Society (ACS), 2021)
In this study, we aimed to shed light on the effects of the Ni-Ca interaction on the activity of the urease enzyme and the incidence of blossom end rot (BER) in tomato (Solanum lycopersicum) fruits. Therefore, Micro-Tom tomato plants were grown under different levels of Ni (0.0 and 1.0 mg dm-3) and Ca2+ (0.35 and 0.70 g dm-3), both alone and in combination. Increased yields and urease activity, as well as inhibition of the incidence of BER, were observed for tomato fruits grown with Ni, even under low Ca availability (0.35 g dm-3). In addition, a microprobe X-ray fluorescence spectroscopy characterization of the distal part of the fruits revealed a sharp decrease in Ca content in the fruits that present BER symptoms.
Keywords: blossom end rot; calcium; nickel; tomato; urease